Effects of experimental warming and nitrogen fertilization on soil microbial communities and processes of two subalpine coniferous species in Eastern Tibetan Plateau, China - Zhao, Chunzhang; Zhu, Liying; Liang, Jin; Yin, Huajun; Yin, Chunying; Li, Dandan; Zhang, Nannan; Liu, Qing (Plant and soil, 2014)
AIM: This study aimed at predicting how sub-alpine coniferous ecosystems respond to global changes in the Eastern Tibetan Plateau by understanding soil microbial communities and activities, as well as variation in the quality and quantity of soil organic matter. METHODS: An experiment was conducted to examine soil microbial communities and their related soil processes in rhizospheric soil of two coniferous species that were exposed to two levels of temperature (unwarmed and infrared heater warming) and two levels of nitrogen (unfertilized and 25 g N m⁻² a⁻¹) from April 2007. RESULTS: Four-year night warming alone slightly affected the phospholipid fatty acid contents of the microbial community. However, the combination of nitrogen addition and soil warming significantly affected soil microbial composition while reducing the biomass of major microbial groups and the activities of most enzymes, especially in Abies faxoniana plots. The combination of warming and nitrogen addition increased soil labile C and N pools in Picea asperata plots and was beneficial for soil recalcitrant C, as well as for labile and total C and N pools in A. faxoniana plots. CONCLUSION: Results indicated that future warming will slightly affect soil microbial communities and their related soil processes. However, warming combined with high nitrogen deposition will significantly constrain soil microbial biomass and enzyme activities, consequently increasing soil C and N pools in sub-alpine coniferous forests of this region.